A multicenter longitudinal study of the prevalence and mortality rate of systemic lupus erythematosus patients in Oman: Oman Lupus Study. (31st May 2021) - Al‐Adhoubi, Nasra K.; Al‐Balushi, Farida; Al Salmi, Issa; Ali, Maha; Al Lawati, Talal; Al Lawati, Batool S. H.; Abdwani, Reem; Al Shamsi, Ali; Al Kaabi, Juma; Al Mashaani, Musallam; Krishna Jha, Divij; Sayed, Sherin; et al.
Abstract: Aim: This study is a longitudinal multicenter study which aims to find the prevalence, the demographic data, survival and mortality rates of patients with systemic lupus erythematosus (SLE) in Oman. Method: All Omani patients, pediatrics and adults diagnosed with SLE, who fulfill either the 1997 American College of Rheumatology or Systemic Lupus International Collaborating Clinics classifications criteria for SLE were included from January 2006 till February 2020. Results: In total 1160 patients were included in this cohort. Data analysis showed that patient's ages ranged from 2‐82 years with female predominance and female‐to‐male ratio of 7:1 (87.7% female, 12.3% male). The mean prevalence of SLE among different age groups was 38.8 (range 5‐63 per 100 000 inhabitants). The mortality rate was found to be 5%. Male patients had significantly higher mortality rate than females (7.6% vs 5.4%, P value = .04). Sepsis was the commonest cause of mortality (34%). The coexistence of systemic sclerosis correlates significantly with death ( P = .002). Survival analysis in our data showed 5, 10, 20, 40‐year survival rates of 100%, 100%, 99% and 90% respectively for antinuclear antibody (ANA) positive patients and lower survival rate for ANA negative patients with 5, 10, 20, 40‐year survival rates of 100, 99%, 99% and 75%, respectively. Conclusion: This study showed that the mean prevalence of SLE in Oman to be 38.8 (range 5‐63) per 100 000 inhabitants. The 40‐year survival rate among patients with positive ANA was found to be 90%, while patients with negative ANA had worse survival outcomes.